Poly(4-vinylaniline)/polyaniline bilayer functionalized bacterial cellulose membranes as bioelectronics interfaces. (15th January 2019) - Rebelo, Ana; Liu, Yang; Liu, Changqing; Schäfer, Karl-Herbert; Saumer, Monika; Yang, Guang
Graphical abstract: Highlights: ATRP combined with COP process to modify PANI coated BC with PVAN interlayer. Formation of an intact PVAN/PANI bilayer of ∼2 μm on the BC membrane. Enhanced electrical conductivity of BC/PVAN/PANI with PVAN grafting. Confirmed SVZ cell viability of PVAN/PANI functionalised BC membrane. Demonstration of BC/PVAN/PANI for construction of potential bioelectronic interfaces. Abstract: Bacterial cellulose (BC) fibers are chemically functionalized with poly(4-vinylaniline) (PVAN) interlayer for further enhancement of electrical conductivity and cell viability of polyaniline (PANI) coated BC nanocomposites. PVAN is found to have promoted the formation of a uniform PANI layer with nanofiber- and nanorod-like supramolecular structures, as an overall augmentation of PANI yield. Compositional and microstructural analysis indicates a PVAN/PANI bilayer of approximately 2 μm formed on BC. The solid-state electrical conductivity of such synthesized BC nanocomposites can be as high as (4.5 ± 1.7) × 10 −2 S cm −1 subject to the amounts of PVAN chemically embraced. BC/PVAN/PANI nanocomposites are confirmed to be thermally stable up to 225 °C, and no signs of cytotoxicity for SVZ neural stem cells are detected, with cell viability up to 90% on BC/PVAN/PANI membranes. We envisage these new electrically conductive BC/PVAN/PANI nanocomposites can potentially enable various biomedical applications, such as for the fabrication of bioelectronic interfaces and biosensors.